Transcriptome analysis of maize seedling roots in response to nitrogen-, phosphorus-, and potassium deficiency - Ma, Nana; Dong, Lina; Lü, Wei; Lü, Jinlian; Meng, Qingwei; Liu, Peng (Plant and soil, 2020)
Aims Soil deficiencies with respect to the availability of macronutrients such as nitrogen, phosphorus, and potassium seriously affect the growth, yield, and grain quality of maize ( Zea mays L.). To improve the utilization efficiency of mineral elements in maize, we wanted to find the key genes that regulate the growth of maize roots under nutrient-deficient conditions. Methods Maize plants were subjected to nitrogen, phosphorus, and potassium deficiency stress and their roots were collected and analyzed using transcriptome sequencing. GO and KEGG analyses of the differentially expressed genes (DEGs) were performed, and qPCR was used to verify the reliability of the transcriptome data. Results When maize was subjected to any of the three nutrient-deficiencies mentioned in Methods , the growth and root vitality of its roots were inhibited. 1255, 1082, and 324 genes specifically expressed when the maize was subjected to N, P, and K deficiencies, respectively, and all three treatments shared 575 DEGs. Genes that are associated with nutrient utilization, hormones, and transcription factors differentially expressed under different types of nutrient-deficiency stress. We speculated that MRP2 , bZIP77 , and bZIP53 play a positive regulatory role in maize root growth in an environment suffering from nutrient deficiencies. Conclusions The molecular mechanism by which maize root growth responds to nutrient stress is complicated. NPF7.3 , GlpT4 , HAK24 , and HAK5 , MRP2 , bZIP77 , and bZIP53 can be used as candidates’ genes that regulate maize root growth under nitrogen, phosphorus, and potassium deficiency stress.